¿Es otra Cosmopolítica Posible? - Blaser, Mario (2018)
This translation of the article - originally published in English - Is anotherCosmopolitics possible? by Mario Blaser makes available to our academic community not only a discussion on a case of conflict between Canadian state institutions, scientific practices and indigenous peoples, comparable with similar conflicts that occur in the Latin American context, but also a good introduction to relatively recent concepts, and relevant ones, to understand these conflicts.